THEORETICAL BASIS OF INCREASING THE ECONOMIC EFFICIENCY OF THE TRANSPORT-LOGISTICS SYSTEM (British Journal of Global Ecology and Sustainable Development, 2024)
In this article, the purpose, tasks and main directions that determine the development of the economic activity of the railway transport-logistics system, the main problems that hinder the effective development of the railway transport-logistics system, directions for the development of the transport-logistics system and the theoretical basis for increasing the economic efficiency of the transport-logistics system are proposed